EFEKTIVITAS TEKNIK PENGERITINGAN RAMBUT POLA ZIGZAG TERHADAP KETAHANAN DAN KARAKTERISTIK BENTUK IKAL RAMBUT - Nabila Adisti; Nayla Rahma; Feni Immanuella Sianturi; Olga Midasa Hutabarat; Asrah Rezki Fauzani; Mutia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the zigzag hair curling technique in producing longer-lasting and more voluminous curls compared to conventional curling techniques. The study used a qualitative descriptive approach through observation of hair curling practices, documentation of curling results, and analysis of hair characteristics after the curling process. The research procedure included hair diagnosis, consultation with the client, selection of the curl size, the zigzag curling process, application of the curling solution, and neutralization. The results showed that the zigzag curling technique was able to produce a more varied curl distribution, increase hair volume, and create a more natural and dynamic curl appearance. Curl durability was influenced by the suitability of the curling technique, the biological condition of the hair, and the accuracy of the hairdresser's initial analysis of the client's chemical treatment history. In addition to technical factors, professional communication between the hairdresser and client also played a crucial role in the success of the curling process. Therefore, the zigzag curling technique can be an alternative learning method for practical and effective salon services in improving the quality of hair curling results.